2012
DOI: 10.3109/14767058.2012.712341
|View full text |Cite
|
Sign up to set email alerts
|

Is breastfeeding duration influenced by maternal attitude and knowledge? A longitudinal study during the first year of life

Abstract: The rate of initiation and overall duration of breastfeeding reached the WHO objectives, but exclusive breastfeeding duration has still not reached satisfactory levels at 6 months. Given that the maternal infant feeding attitude is the only factor independently related to breastfeeding duration for the whole first year of life, reliable measures of maternal attitude could be used as a first step in targeting and assessing interventions that promote and sustain breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…Mothers who are predisposed towards breastfeeding are consistently found to have greater duration of breastfeeding regardless of intensity [ 7 , 45 ]. Those mothers who believe that breastfeeding is more convenient, healthier and cheaper are less likely to introduce formula to their infant than those who find breastfeeding to be embarrassing, restrictive or uncomfortable [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mothers who are predisposed towards breastfeeding are consistently found to have greater duration of breastfeeding regardless of intensity [ 7 , 45 ]. Those mothers who believe that breastfeeding is more convenient, healthier and cheaper are less likely to introduce formula to their infant than those who find breastfeeding to be embarrassing, restrictive or uncomfortable [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several global studies were conducted that evaluated primarily the attitudes and behavior of mothers in relation to exclusive breastfeeding. Most of these studies were conducted in developing countries [12,13,14,15,16,17,18,19,20,21], and only few were run in industrialized countries [22,23,24,25,26,27]. Therefore, the present survey aims to investigate the knowledge, attitudes, and practices of women towards exclusive breastfeeding to determine their reasons for why breastfeeding was interrupted or not carried out, and analyze the factors associated with knowledge and practices surrounding exclusive breastfeeding in the six first months of their child’s life.…”
Section: Introductionmentioning
confidence: 99%
“…In GCC countries, research found that breastfeeding knowledge among studied participants was highly adequate [12]. However, continued breastfeeding practices at one year were not sufficient, and was negatively influenced by mother’s attitudes toward breastfeeding [13]. In addition, some breastfeeding practices have contributed to continued breastfeeding at one year of age, including mother–infant skin-to-skin contact (SSC) after birth, which was shown as an efficient method in supporting the continuation of breastfeeding [14].…”
Section: Introductionmentioning
confidence: 99%